Effectiveness and safety of glucocorticoid combined with RAAS inhibitors for treatment of IgA nephropathy - ZHOU Ying; ZHANG Li-wen; HUANG Wei; LIU Yun-zi; WANG Wei-ming (Linchuang shenzangbing zazhi)
Objective To retrospectively compare the clinical efficacy and safety of RAAS inhibitor and combination of RAAS inhibitor with glucocorticoid for treatment of IgA nephropathy.Methods A total of 263 patients diagnosed with IgA nephropathy by renal biopsy in Ruijin Hospital from June 2009 to June 2016,with eGFR ≥45 mL·min-1·（1.72 m2）-1 and 24-hour urinary protein > 0.5 g/d,were collected and divided into simple RAAS inhibitor group and RAAS combined with glucocorticoid group.The clinical biochemical indicators,pathological parameters,adverse events and prognosis were compared between various regimes.Results The RAAS inhibitor combined with glucocorticoid group was superior to the simple RAAS inhibitor group in terms of urinary protein reduction and renal function improvement（P<0.05）,and had a higher incidence of infection in the short term（6 months）（21.4% vs. 9.9%,P<0.05）,but a lower incidence of adverse events（9.8% vs. 28%,P<0.01）.Kaplan-Meier survival analysis showed that the long-term prognosis of the combination therapy is better than that of the simple treatment groupeven in patients with 24-hour urinary protein 0.5～1.0 g/d.Multivariate Cox regression model showed that the combination therapy（HR 0.304,95% CI 0.148～0.627）,complete remission of 24-hour urine protein in 6 months of treatment（HR 0.369,95% CI 0.171～0.798）,and T1/0 in pathological type（MEST-C scores）（ HR3.513,95% CI 1.536～8.035）were independent risk factors for prognosis.Conclusions A combination of RAAS inhibitor with glucocorticoid can effectively improve proteinuria and eGTR,and has a lover incidence of adverse events.Glucocorticoid combination therapy,complete remission of urinary protein in 6 months of treatment is independent protective factors for renal prognosis,while T1/0 is the independent risk factor.